An experimental comparative study of the stabilization mechanism of biogas-hydrogen diffusion flame. (15th January 2019) - Zhen, H.S.; Wei, Z.L.; Chen, Z.B.; Xiao, M.W.; Fu, L.R.; Huang, Z.H.
Abstract: This work describes an experimental study of the effect of hydrogen addition on the stabilization characteristics of laminar biogas diffusion flame. The focus is to identify and compare various factors influencing the blowoff process. Three compositions of biogas, BG40, BG50 and BG60 were considered and the amount of hydrogen added was varied from 5% to 25% of the biogas by volume. With increasing hydrogen addition, the critical flow velocity beyond which the flame blows off increases faster than the laminar burning velocity (LBV) does, indicating that flame stabilization is not solely dependent on laminar burning velocity. An exponential relationship is observed between LBV and flame propagation speed. Therefore, both flame propagation speed and LBV, together with other factors, contribute to flame stabilization. The reason for no stable lift for either biogas or H2 -biogas flame is analyze by Schmidt number calculation, and the results agree with the literature. Also found is that hydrogen added to biogas accelerates the fuel mass diffusion, which may play an important role for stabilization of the nozzle-attached flame. The CO2 -C3 H8 and BG60 flames were compared to exclude the possible dominant role played by insufficient heat release and/or excessive heat loss due to CO2 present in biogas. Tested on varied-size burners show that flame stabilization depends on burner pore size, where larger diameter allows better flame stability. The universal equation for predicting blowout/blowoff velocity in the literature was found to be invalid for H2 -enriched biogas flame and a new scaling law was put forwards. Highlights: No stable lifted biogas or H2 -enriched biogas flame agrees with critical Schmidt number criterion. Hydrogen addition increases fuel mass diffusivity, and may be important for flame stabilization. Propane addition promotes flame stability, but much less significantly than hydrogen addition. Flame curvature weakens the flames stability.